Audit of documentation accompanying referred maternity cases to a referral hospital in northern Ghana: a mixed-methods study - Edward Kwabena Ameyaw; Roberta Mensima Amoah; Carolyne Njue; Nguyen Toan Tran; Angela Dawson (BMC, 2022)
Abstract Background Effective referral of maternity cases, which cannot be managed at the primary healthcare level, with detailed referral forms is important for reducing possible delays in the provision of higher-level healthcare. This is the first study to audit documentation or referral forms that accompany referred maternity cases to a referral hospital in the northern region of Ghana. Materials and methods This study employed an explanatory sequential mixed-method design, starting with a quantitative review of referral forms that accompanied all patients referred to four units (antenatal, antenatal emergency, labour and neonatal intensive care) of a referral hospital in northern Ghana. In-depth interviews were held with the heads of the four units afterwards. Descriptive statistics were computed for the quantitative data. The qualitative data was subjected to content analysis. Integration of the data occurred at the data interpretation/discussion level. Results A total of 217 referral forms were analysed. Nearly half of the cases were referred from the Tamale Metropolis (46.5%) and 83.9% were referred for advanced care, whilst 8.3% were referred due to a lack of medical logistics and equipment such as oxygen and skilled personnel (6%). Completion rates of the referral forms were as follows: < 50% completion (n = 81; 37.3%), 50-75% completion (n = 112; 51.6%) above 75% completion (n = 24; 11.1%). Some of the handwriting were not legible and were quite difficult to read. The key informants stated that incomplete forms sometimes delay treatment. The head of the antenatal care unit at the referral hospital suggested professional development sessions as a strategy for supporting clinicians to fill the forms as expected. Conclusion The Ghana Health Service should conduct regular audits, develop job aides and provide incentives for health professionals who accurately complete referral forms. Completing forms and digitizing health records can help ensure further efficiencies in the health information system and sustain good maternity referral documentation practices.